Role of Umbilical Artery Doppler in Predicting Intrauterine Growth Restriction and Foetal Outcome in Pregnant Ladies with Pregnancy Induced Hypertension (Nepalese Journal of Radiology, 2018)
Introduction: Umbilical artery Doppler is a noninvasive tool in the evaluation of the foetal and uteroplacental circulation. The aim of this study was to evaluate the role of umbilical artery Doppler in pregnancy induced hypertension (PIH) ladies with clinical suspicion of intrauterine growth restriction (IUGR) and to predict the fetal outcome.Methods: A total of 44 singleton pregnancies beyond 34 weeks of pregnancy complicated with pregnancy induced hypertension and clinical suspicion of intrauterine growth restriction were evaluated using ultrasonography and Doppler. Six pregnant ladies were excluded from the study. The umbilical artery systolic/diastolic (S/D) ratio was calculated from a free loop of cord midway between the placenta and insertion of cord. All the pregnant ladies were followed up till delivery. Birth weight, adverse foetal outcome were recorded. Babies were divided into two groups, small for gestational age (SGA) and appropriate for gestational age (AGA) based on Lubchenco growth chart. SGA was considered as IUGR.Results: Abnormal S/D in umbilical artery was seen in 26 pregnant ladies, out of which 22 had an abnormal resistive index (RI). Umbilical artery S/D ratio had a sensitivity of 66.7% and specificity of 28.57%, in diagnosing IUGR. Umbilical artery RI had a sensitivity of 50% and specificity of 28.6% in diagnosing IUGR. Similarly, S/D ratio of the umbilical artery had a sensitivity of 100 %, specificity of 46.2%, in diagnosing adverse foetal outcome. RI was 100% sensitive in diagnosing foetal outcome.Conclusion: Umbilical artery Doppler plays an important role in PIH in diagnosing IUGR and predicting a foetal outcome.